2015
DOI: 10.1007/s11829-015-9366-z
|View full text |Cite
|
Sign up to set email alerts
|

Temperature alters the interaction between a herbivore and a resistant host plant

Abstract: Temperature and other environmental factors can strongly influence arthropods and their interactions with host plants. However, such effects are usually studied while keeping the suitability of host plants as constant as possible, thereby removing the possibility of interactions between temperature and host plant resistance. We performed experiments to determine whether temperature interacts with plant resistance to alter the density, movement, and distribution of wingless soybean aphids on resistant and susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The variation among temperatures used for these experiments could be a possible explanation for the differences in results. Furthermore, there may be interactions between abiotic factors, like temperature, on the impact of Rag genes [ 37 , 38 ]. However, the extent that the protection from all Rag genes is influenced by temperature is unknown [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The variation among temperatures used for these experiments could be a possible explanation for the differences in results. Furthermore, there may be interactions between abiotic factors, like temperature, on the impact of Rag genes [ 37 , 38 ]. However, the extent that the protection from all Rag genes is influenced by temperature is unknown [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other lines can have variable susceptibility depending on temperature (Richardson 2012). Whalen and Harmon (2015) also demonstrated that overall soybean aphid population growth increases as temperature increases on susceptible plants, but decreases as temperature increases on resistant plants. In addition, Brunner et al (2014) found an inverse relationship between soybean aphid number and the number of root nodules, which can affect the amount of nodule‐colonizing bacteria and thereby affect N availability.…”
Section: Discussionmentioning
confidence: 88%
“…This is in line with a similar study on soybean aphids ( Aphis glycines Matsumura), where increased temperatures had a positive effect on their abundance on susceptible soybean [ Glycine max (L.) Merr.] varieties and a negative effect on their abundance on resistant ones (Whalen & Harmon, 2015). These findings were partly attributed to the accelerating effect of a higher temperature on infestation parameters (i.e., soybean aphids would die either way on resistant soybeans, but this process is accelerated for high temperatures).…”
Section: Discussionmentioning
confidence: 99%